The slow disappearance of the Syriacs from Turkey and of the grounds of the Mor Gabriel Monastery - Omtzigt, Pieter (Lit-Verl., 2012)
Foreword / Pieter Omtzigt -- Introduction / William Dalrymple -- Part 1: The Syriacs. The collapse of the Ottoman Empire and the 'Seyfo' against the Syrians / Martin Tamcke -- The Lausanne Treaty : high aspirations, highly neglected / Alan Hurst -- Who are the Syriacs? / Herman Teule -- The Syrian Orthodox Church / Jens Nieper -- Living between the fronts : the Turkish-Kurdish conflict and the Assyrians / Aryo Makko -- Turkey : secularism with an Islamic flavour and persisting obstacles to religious freedom / Dennis Pastoor -- Minority rights in Turkey : quo vadis, Assyrians? / Soner Onder -- Almost a miracle - Syriacs are returning to their homelands / Horst Oberkampf -- Cadastral registration of lands and preservation orders in Turkey's south-east : subtle forms of discrimination? / Markus Tozman -- The role of religious freedom in the context of the accession negotiations between the European Union and Turkey - the example of the Arameans / Renate Sommer -- Persecution of Christians in Turkey / Ingrid Fischbach -- Part 2: The Mar Gabriel Monastery. The Monastery of Mor Gabriel : a historical overview and its wider significance today / Sebastian Brock -- Reconciled by Mor Gabriel / Baskin Oran -- The Saint Gabriel Monastery Trust / Yakup Bilge -- St. Gabriel and religious freedom in Turkey / Gus Bilirakis -- Mor Gabriel : a symbol of how the Turkish state deals with its religious minorities / Ute Granold -- United for the sake of the Mor Gabriel Monastery / Naures Atto -- Interview with Sébastien de Courtois / Pieter Omtzigt -- Appendix 1: Initiative policy document : The alarming situation of the Monastery of Mor Gabriel and the Aramaic-speaking Christians in Turkey - the Syriacs / Pieter Omtzigt -- Appendix 2: The disappeared documents from St. Gabriel Monastery's case file / Baskin Oran